Potensi Wisata Kuliner Kota Surakarta dan Strategi Mengembangkan Wisata Kuliner Kota Surakarta. - Made Prasta (Jurnal Pariwisata Indonesia, 2021)
Surakarta city is a city that has a variety of tourism, such as cultural tourism, educational tourism, historical tourism and culinary tourism. Surakarta city has abundant culinary tourism such as nasi liwet, tengkleng and sate kere. In this article will discuss about the potentials of culinary tourism Surakarta City, how to develop culinary tourism and key factors of successful development of culinary tourism. This article uses observation research methods and library studies.